Determinación de los actuales valores del turismo y la imagen de las empresas de hospedaje de la ciudad de Iquitos - Amasifuen Apuela, Robert (2023)
The thesis: "determination of the current values of tourism and the image of the lodging companies of the city of Iquitos". It is a descriptive study under a quantitative and applied research model approach because it studies a problem, with a non-experimental design with an empirical-applied methodology because it is a case study. The population was the officials and workers of the lodgings of the city: Hotels, Hostels and Lodges. The sample is non-probabilistic and intentional, 60 surveys, 10 lodges, 30 hotels and 20 hostels were applied. The questionnaire has 20 items with 5 alternatives according to the Likert scale, they were processed with the Spss 25 system, the data and information achieved the objectives, demonstrating the hypothesis. These results have been obtained from the friendliness and reputation of the hosting companies; the values of inclusion and kindness; sustainability and satisfaction; of professionalism and confidence to finally accept the hypothesis "A greater practice of tourism values will increase the good image of lodging companies".